Review: Perbandingan antara Standard Half-Life (SHL) dan Extended Half-Life (EHL) Replacement Therapy berbasis Real-World Evidence (RWE) - Sudirman, Agriawan; Suharjono, Suharjono; Nasir, Ahmad; Safarudin, Rudi (JSFK (Jurnal Sains Farmasi & Klinis), 2022)
Hemophilia is a common hereditary coagulation blood disorder due to the deficiency activity of clotting factors. Hemophilia is divided into two, namely hemophilia A and hemophilia B. Among all treatments, standard half-life (SHL) and extended half-life (EHL) factor replacement products are the most commonly used. This study aimed to review real-world evidence on the comparison of SHL and EHL. A literature search was conducted in PubMed and google scholar published from 2017 to 2021. There were 10 articles that met the criteria. Based on the synthesis results, the total proportion of patients using EHL factor concentrates for both onâ€demand and prophylactic factor replacement therapy increased. Recent evidence reveals that EHL may reduce the number of infusions, increase factor trough levels, and substantially decrease the annual bleeding rate. Efficacy-wise, EHLs unquestionably have better performances than SHLs; however, the EHL products seem to be too expensive to be utilized as the primary standard of care for hemophilia. However, the economic aspect of the replacement factor switching still required more in-depth studies.